Strengthening Innovation Culture In A Mining Company's Transformation In Indonesia - Najib Arangi Panjah; Achmad Fajar Hendarman (Dinasti Publisher, 2025)
Innovation is a key driver of competitiveness and sustainability, particularly for industries undergoing strategic transformation. This study explores organizational innovation culture using a mixed-method approach, integrating quantitative assessment and qualitative insights. The Innovation Quotient (IQ), which comprises six building blocks : values, behaviors, climate, resources, processes, and success; served as the primary assessment framework. Data were collected through surveys and semi-structured interviews across various organizational levels. Findings reveal strengths in areas such as corporate values and internal collaboration. However, gaps were identified in leadership behaviors supporting innovation, resource allocation, and the absence of formalized innovation processes. These shortcomings suggest critical barriers to institutionalizing innovation. The research assumes that corporate culture significantly influences innovation outcomes, and that systematic evaluation can yield actionable insights. This research assumes that organizational culture influences innovation outcomes and that systematic evaluation can identify practical improvements. It contributes to both academic and managerial perspectives by applying the IQ model in the mining industry. Practical recommendations include developing structured innovation leadership programs, allocating dedicated innovation resources, and embedding innovation metrics into strategic planning. These actions aim to foster a more adaptive and innovation-conducive organizational culture.